2000
DOI: 10.1302/0301-620x.82b7.0820959
|View full text |Cite
|
Sign up to set email alerts
|

Fix and flap: the radical orthopaedic and plastic treatment of severe open fractures of the tibia

Abstract: We performed a retrospective review of the case notes of 84 consecutive patients who had suffered a severe (Gustilo IIIb or IIIc) open fracture of the tibia after blunt trauma between 1990 and 1998. All had been treated by a radical protocol which included early soft-tissue cover with a muscle flap by a combined orthopaedic and plastic surgery service. Our ideal management is a radical debridement of the wound outside the zone of injury, skeletal stabilisation and early soft-tissue cover with a vascularised mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(154 citation statements)
references
References 28 publications
(38 reference statements)
7
145
0
2
Order By: Relevance
“…Concerted efforts of the plastic surgeon and orthopaedic surgeon have improved treatment of complex foot and ankle wound problems that once may have been considered unsalvageable, particularly in the case of open fractures [7,11,13,14]. The orthoplastic approach, which integrates the expertise and surgical techniques of the two specialties, also may permit improvements in the management of foot and ankle problems that are not related to trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Concerted efforts of the plastic surgeon and orthopaedic surgeon have improved treatment of complex foot and ankle wound problems that once may have been considered unsalvageable, particularly in the case of open fractures [7,11,13,14]. The orthoplastic approach, which integrates the expertise and surgical techniques of the two specialties, also may permit improvements in the management of foot and ankle problems that are not related to trauma.…”
Section: Discussionmentioning
confidence: 99%
“…All six studies [6,15,16,29,35,45] with data regarding flap rates and extended negative pressure wound therapy use reported a decrease in flap procedures with extended negative pressure wound therapy. Two [15,16] of the studies reported infection complications similar to those of historic controls [1,11,13,20,26,28]. Dedmond et al [15,16] concluded the avoidance of flap procedures, particularly in the pediatric population, in the end outweighed the equivalent infection rates.…”
Section: Does Negative Pressure Wound Therapy Facilitate Late Flap Prmentioning
confidence: 94%
“…The question was whether use of negative pressure wound therapy beyond 72 hours would result in increased infection rates compared with historic controls [1,11,13,20,26,28]. Reported infection rates are highly variable for Grade IIIB tibia wounds with the upper end at 67% [10].…”
Section: Does Negative Pressure Wound Therapy Facilitate Late Flap Prmentioning
confidence: 99%
“…The classic studies by Godina (26) and Gopal et al (27) , who performed early closure of injury or early flap rotation, demonstrate significantly reduced infection rates, even in severe open fractures.…”
Section: Open Tibial Fracture -Primary or Delayed Closure?mentioning
confidence: 97%